A water-soluble bithiophene with increased photoluminescence efficiency and metal recognition ability. Issue 35 (25th August 2020) - Delgado-Pinar, Estefanía; Pineiro, Marta; Sérgio Seixas de Melo, J.
Abstract : A water soluble and highly fluorescent bithiophene was obtained. The excited state behavior is fully characterized and with tert -butylsulfonamide derivatization the recognition of Cu(ii ) and Hg(ii ) with high selectivity was observed. Abstract : A new water-soluble tri- tert -butyl-bithiophenesulfonamide (α2-tbS ) was synthesized and a comprehensive spectroscopic and photophysical study was undertaken in organic solvents and water at different pH values. In contrast to the behaviour found for the parent (and un-substituted) α, α′-bithiophene (α2 ), in which radiationless decay processes are the main excited-state deactivation channels, the tert -butylsulfonamide derivative presents a significant fluorescence quantum yield ( ϕ F ) ( ca. one order of magnitude higher than that of α2 ). The high ϕ F allowed further exploring α2-tbS as a selective fluorimetric sensor for metal ions. A strong selectivity towards Cu(ii ) is observed at neutral pH values, whereas at pH = 9.5 a strong quenching upon the addition of Hg(ii ) is observed. An additional high sensitivity of 0.64 ± 0.02 ppm towards Cu(ii ) was observed, well below 1.25 ppm (∼20 μM), the maximum value allowed in drinking water by the EPA.